The oral art of Soqoṭra (Leiden ; Boston)
3 cilt (1. c. xix, 543 sayfa ; 2. c. xi, sayfa [545]-1562 ; 3. c. xi, sayfa [1565]-2443)
Keywords: “In the bilingual English-Arabic work, The Oral Art of Soqoṭra: A Collection of Island Voices, Miranda Morris, in collaboration with Soqoṭrans from all parts of the island, present over a thousand examples of poems and songs, prayers, lullabies, work-chants, messages in code, riddles, examples of community wisdom encapsulated in poetic couplets, and stories cenetred on a short poem or exchange of poems. These were documented by oral transmission directly to the scholars, or through recordings collected. They are presented in Soqoṭri (transcribed phonetically in Roman and in Arabic script), and in English and Arabic translation.“ --